A general introduction to the Bible - Grannan, Charles P. (B. Herder book co., 1921)
1. Definition, names, divisions of the Bible; history of the original languages; history of the original texts; history of the ancient versions -- 2. Textual Biblical criticism; higher Biblical criticism; Biblical archaeology -- 3. Inspiration of the Bible; history of thecanon -- 4. Biblical hermeneutics; Biblical exegis.